Home Literacy Environment and Children’s English Language and Literacy Skills in Hong Kong - Lau, Carrie; Richards, Ben (Frontiers in Psychology, 2021)
Emerging evidence has shown a positive association between the home literacy environment (HLE) and monolingual children’s language and literacy development. Yet, far fewer studies have examined the impact of the HLE on second language development. This study examined relations between the HLE and children’s development of English as a second language in Hong Kong. Participants were 149 ethnic Chinese children (80 girls; Mage = 59 months, SDage = 10 months) and one of their caregivers. Caregivers completed questionnaires about their family backgrounds and HLE and children were assessed on their English language and literacy skills. Findings revealed considerable variability in the types of literacy activities that caregivers were engaged in at home with their children. A series of multilevel regressions demonstrated that the HLE was differentially associated with English vocabulary, letter knowledge, phonological awareness, and word reading skills after controlling for child and family characteristics. Results highlight the importance of a literacy-rich home environment for children’s development of English as a second language and the need to support caregivers in providing a range of home literacy activities to facilitate different language and literacy skills.